Artificial Intelligence and Legal Certainty in Determining Ramadan and Syawal for Muslim Religious Observance - Sayehu; Usman; Hidayat, Ahmad; Setiadi, Agung Heru (UIN K.H. Abdurrahman Wahid Pekalongan, 2025)
This study explores the role of Artificial Intelligence (AI) in reinforcing legal certainty for Muslims in determining the beginning of Ramadan and Syawal through the optimization of traditional methods—Hisab (astronomical calculations) and Rukyat (moon sighting). Employing a qualitative approach, this research analyzes scholarly literature, case studies, and existing technological models to evaluate how AI can enhance precision, objectivity, and legitimacy in lunar calendar determinations. The findings reveal that AI-based tools, including machine learning algorithms and image recognition systems, not only improve the accuracy of Hisab but also automate Rukyat by processing real-time meteorological and astronomical data. By integrating AI into these methods, the study proposes a hybrid model that supports religious observance with scientifically validated outcomes, ultimately contributing to greater legal certainty and unity among Muslim communities. This research highlights AI's potential to bridge traditional Islamic jurisprudence and technological innovation in support of timely and consistent religious practices.